Finite Element Analysis of Cellular Structures Using Ansys - Abdon Siqueira Castilho Ferreira, Izabella; Alkentar, Rashwan; Gurbanov, Oghuz; Jean Moraes De Lima, Caio; Miguel De Medeiros Bortolini, Arthur (International Journal of Engineering and Management Sciences, 2021)
Additive manufacturing (AM) is a process in which the product is composed of overlapping layers of a material that is added using devices such as 3D printers. Its process has been evolving for decades and nowadays it can be used for several applications and with different materials. One modern usage is for medical and dental purposes. Since it became possible to print metal, it has been a good solution for bone implants, once it must be done with biomaterials and can now replicate the bone structure, for that unit cells should compose the implant. Both conditions are now possible to be achieved by AM, and the current study will analyze, using finite element method, the possibilities to create specimens for tests which the final product would result in a 3D printed bone implant.